Terapia assistida por cães em crianças com síndrome congênita do Zika Vírus - Cruz, Tarciane Marinho Albuquerque de Vasconcellos (2020)
Introduction: After an epidemic associated with the Zika virus, the birth of a child began to bring fear with the possibility of a baby being born with the diagnosis of Congenital Zika Virus Syndrome. Some children with this diagnosis have changes in neuropsychomotor development and need care in order to reduce these changes. An alternative to care assistance consists on Therapy Assisted by Dogs, which is a complementary therapeutic intervention for stimulation that focus on the benefits existing within the bond between humans and animals. Objective: Implement Dog Assisted Therapy to stimulate children with Congenital Zika Virus Syndrome. Method: Intervention research of the type before / after, with a qualitative approach, carried out in a reference institution for disabled persons, in partnership with the Dogs of Paraíba Military Police. The research participants were health professionals, children diagnosed with Zika Virus Syndrome and mothers of these children. The data collection occurred between the months of February of October 2019, and was carried out at the site of Early Stimulation Service. The forms of collection were the semi-structured interview by recording recording, however for how the recording resource was used, as well as a field diary. The data were analyzed according to the Inductive Thematic Analysis and based on Bronfenbrenner's Ecological Theory. Results: Dog Assisted Therapy was well accepted by both parents and professionals who assisted the children, and both agreed that enabled the improvement of abilities previously not performed by children affected by the syndrome, such as spontaneous opening of hands, greater cephalic control, socioenvironmental interaction, social smile, breaking tension patterns, decreased irritability and convulsive episodes. Conclusion: The results suggest that Dog Assisted Therapy can contribute to early stimulation, in order to bring the mitigation of changes on the delayed neuropsychomotor development of children with Congenital Zika Virus Syndrome, through an innovative, low-cost and benefic strategy; and thus, collaborate to promote health and stimulate child development.